Acquisition and performance of sports skills - McMorris, Terry (Wiley SportTexts series, 2014)
An extensive update of a successful textbook on skill acquisition for sport students. Praised for its clarity of writing style and presentation the new edition will be an essential buy for those needing a practical, sport-focused introduction to the theory and application of human motor skills